Prosthetic and Surgical Approach for Oral Rehabilitation in a Patient with Amelogenesis Imperfecta: A Clinical Report - H. Sazegara; K. Seyedan; H. Behnia; P. Ghaderi (Tehran University of Medical Sciences, 2007)
Amelogenesis imperfecta is a heterogeneous group of hereditary disorders. Its treatment continues throughout the patients' childhood and adolescence and consists of advanced restorative care in severe cases. A thorough prosthodontic treatment plan including orthognatic surgery, full veneer crowns and all ceramic anterior crowns is presented in this clinical report.